A regression model for predicting the shear strength of RC knee joint subjected to opening and closing moment. (September 2021) - Tariq, Moiz; Khan, Azam; Shayanfar, Javad; Hanif, Muhammad Usman; Ullah, Asad
Abstract: An efficient non-linear model is developed to estimate the shear strength of the reinforced concrete (RC) beam-column knee joint subjected to reverse cyclic loading, which produces two distant types of the moment: either opening moment or closing moment in the knee joint. A regression-based approach is used to develop two separate and effective equations for predicting the knee joint shear strength under the opening and the closing moment. The influence of various material and geometric factors like concrete compressive strength, joint aspect ratio, and strength of tensile or compressive reinforcement is taken into account. A database containing 61 shear strength experiments of the knee joint is statistically analysed based on the variation in these factors and is used to formulate the proposed equations. These equations are also statistically compared and analysed with the previously proposed models. Overall, the proposed equations can forecast the RC knee joint shear strength with reasonable accuracy and render the proposed equations ideal for practical application. Highlights: A regression-based model estimating the shear capacity of RC knee joint. The model is adapted to incorporate different influencing factors. Knee joint opening and closing moments are captured by two separate models. The results offered by the model are better than the current structural design codes.